Assessment of response rates and yields for Two opportunistic Tools for Early detection of Non-diabetic hyperglycaemia and Diabetes (ATTEND). A randomised controlled trial and cost-effectiveness analysis. (August 2016) - Khunti, K.; Gillies, C.L.; Dallosso, H.; Brady, E.M.; Gray, L.J.; Kilgallen, G.; Willis, A.; Zafar, A.; Davies, M.J.
Highlights: Both the LPCRS and the LSAS incur relatively low costs to implement. Both scores successfully identified new cases of type 2 diabetes. The LPCRS resulted in a higher rate of individuals proceeding to blood test. Abstract: Aims: To assess the opportunistic use in primary care of a computer risk score versus a self-assessment risk score for undiagnosed type 2 diabetes. Methods: We conducted a randomised controlled trial in 11 primary care practices in the UK. 577 patients aged 40–75 years with no current diagnosis of type 2 diabetes were recruited to a computer based risk score (Leicester Practice Computer Risk Score (LPCRS)) or a patient self-assessment score (Leicester Self-Assessment Score (LSAS)). Results: The rate of self-referral blood tests was significantly higher for the LPCRS compared to the LSAS, 118.98 (95% CI: 102.85, 137.64) per 1000 high-risk patient years of follow-up compared to 92.14 (95% CI: 78.25, 108.49), p = 0.022. Combined rate of diagnosis of type 2 diabetes and those at risk of developing the disease (i.e. impaired glucose tolerance (IGT) or impaired fasting glucose (IFG)) was similar between the two arms, 15.12 (95% CI: 9.11, 25.08) per 1000 high-risk patient years for LPCRS compared to 14.72 (95% CI: 9.59, 22.57) for the LSAS, p = 0.699. For the base case scenario the cost per new case of type 2 diabetes diagnosed was lower for the LPCRS compared to the LSAS, £168 (95% Credible Interval (CrI): 76, 364), and £352 (95% CrI: 109, 1148), respectively. Conclusions: Compared to a self-assessment risk score, a computer based risk score resulted in greater attendance to an initial blood test and is potentially more cost-effective.